Palliative care in interstitial lung disease: living well - Kreuter, Michael (The lancet. Respiratory medicine, 2017)
Summary Progressive fibrotic interstitial lung diseases (ILDs) are characterised by major reductions in quality of life and survival and have similarities to certain malignancies. However, palliative care expertise is conspicuously inaccessible to many patients with ILD. Unmet patient and caregiver needs include effective pharmacological and psychosocial interventions to improve quality of life throughout the disease course, sensitive advanced care planning, and timely patient-centred end-of-life care. The incorrect perception that palliative care is synonymous with end-of-life care, with no role earlier in the course of ILD, has created a culture of neglect. Interventions that aim to improve life expectancy are often prioritised without rigorous assessment of the individual's health and psychosocial needs, thereby inadvertently reducing quality of life. As in malignant disorders, radical interventions to slow disease progression and palliative measures to improve quality of life should both be prioritised. Efficient patient-centred models of palliative care must be validated, taking into account religious and cultural differences, as well as variability of resources. Effective implementation of palliative care for ILD will require multidisciplinary participation from clinicians, specialist nurses, psychologists, social workers, and, in some countries, non-governmental faith and community-based organisations with access to palliative care expertise.